Design of SAR image feature detector for small-scaled coherent change detection - Kee Woong Lee; Hyun-Chul Kim; Bumseung Kim; Woo-Kyung Lee (IEEE International Geoscience and Remote Sensing Symposium proceedings, 2016)
Recently multi-band, high-resolution SAR images acquired from spaceborne payloads are produced on daily basis and easily available world-widely. Although the change detection techniques for SAR images have been long studied, demands for developing small-scaled change detection method algorithm are growing with the rise of SAR image features. Among others, the small-scaled change detection method is a topic of high interest in military applications for establishing future national security systems. SAR images are distinguished from optical images due to the complex nature of the inherent phase information in conjunction with amplitude parameters. The performance of detection of changes through SAR imaging are highly dependent upon both ACD(Amplitude Change Detection) and CCD(Coherence Change Detection). The ACD method, based on measurement of amplitude, is the most common approach. It simplifies the technical mechanism of imaging as it is sensitive to changes caused by artificial objects and buildings on land. The CCD method, using the information on phase, measures the extent of similarities of multi-temporal images or their coherences. In this paper, CCD algorithms are adopted to detect local changes in dense urban areas acquired from spaceborne SAR payloads. It will be further perceived to construct efficient monitoring systems on strategic target areas.